Depletion of Cultivatable Gut Microbiota by Broad-Spectrum Antibiotic Pretreatment Worsens Outcome After Murine Stroke. Issue 5 (May 2016) - Winek, Katarzyna; Engel, Odilo; Koduah, Priscilla; Heimesaat, Markus M.; Fischer, André; Bereswill, Stefan; Dames, Claudia; Kershaw, Olivia; Gruber, Achim D.; Curato, Caterina; Oyama, Naoki; Meisel, Christian; et al.
Abstract : Background and Purpose—: Antibiotics disturbing microbiota are often used in treatment of poststroke infections. A bidirectional brain–gut microbiota axis was recently suggested as a modulator of nervous system diseases. We hypothesized that gut microbiota may be an important player in the course of stroke. Methods—: We investigated the outcome of focal cerebral ischemia in C57BL/6J mice after an 8-week decontamination with quintuple broad-spectrum antibiotic cocktail. These microbiota-depleted animals were subjected to 60 minutes middle cerebral artery occlusion or sham operation. Infarct volume was measured using magnetic resonance imaging, and mice were monitored clinically throughout the whole experiment. At the end point, tissues were preserved for further analysis, comprising histology and immunologic investigations using flow cytometry. Results—: We found significantly decreased survival in the middle cerebral artery occlusion microbiota-depleted mice when the antibiotic cocktail was stopped 3 days before surgery (compared with middle cerebral artery occlusion specific pathogen-free and sham-operated microbiota-depleted mice). Moreover, all microbiota-depleted animals in which antibiotic treatment was terminated developed severe acute colitis. This phenotype was rescued by continuous antibiotic treatment or colonization with specific pathogen-free microbiota before surgery. Further, infarct volumes on day one did not differ between any of the experimental groups. Conclusions—: Conventional microbiota ensures intestinal protection in the mouse model of experimental stroke and prevents development of acute and severe colitis in microbiota-depleted mice not given antibiotic protection after cerebral ischemia. Our experiments raise the clinically important question as to whether microbial colonization or specific microbiota are crucial for stroke outcome. Abstract : Supplemental Digital Content is available in the text.